Experience of Engagement in a Somatosensory Discrimination Intervention for Children with Hemiplegic Cerebral Palsy: A Qualitative Investigation. (4th July 2019) - McLean, Belinda; Girdler, Sonya; Taylor, Susan; Valentine, Jane; Carey, Leeanne; Elliott, Catherine
ABSTRACT: Background : To successfully modify an intervention from an adult population for use with children with cerebral palsy, it is important to understand the components that support a child's motivation and engagement. Method : Ten children who had participated in the Sense© intervention (mean age = 11 years 2 m [SD = 2 years]; four males; Manual Ability Classification System level I = 1, II = 9) and their primary caregivers ( N = 11, 10 females) were interviewed. Transcripts were analyzed using framework analysis. Results : Key themes were identified in the core domains of the Synthesis of Child, Occupational Performance and Environment in Time model. Child: children's somatosensory discrimination ability improved; Motivation: incorporating child's goals was essential, as were real-world gains; Environmental: parents were interested in having more involvement in the intervention. Conclusion : The most engaging elements of the intervention for children were the attainment of their self-selected goals. Opportunities to modify the intervention for improved partnership with parents were identified.